Honey on brain health: A promising brain booster - Zamri, Nurul Ashykin; Ghani, Nurhafizah; Ismail, Che Aishah Nazariah; Zakaria, Rahimah; Shafin, Nazlahshaniza (Frontiers in Aging Neuroscience, 2023)
Since ancient times, honey has been employed in many aspects of everyday life, the most popular of which is as a natural sweetener. Honey is used not only as a nutritional product but also in health as a supplement and various applications which can be found especially related to brain health. Brain health is the capacity to carry out all mental functions necessary for cognition, such as the capacity to learn and judge, utilize language, and recall. This review presents the current trend of research on honey, particularly the interest in underlying mechanisms related to brain booster health. A total of 25 original articles addressing brain health from the consumption of honey were analyzed. We identified four main brain health benefits which are memory booster, neuroprotective effect, anti-stress and anti-nociceptive with the proposed underlying mechanism. The contribution of honey in brain health research has received attention to focus on exploring the relationship between honey, brain health and the mechanism. The findings from this review may be potentially beneficial to develop new therapeutic roles for honey in which to help to determine the best and most promising to benefit and boost overall brain health.